Sports Infrastructure Development Strategy in the Region Medan city - Akus Harmoko; Abdiyanto; Abdi Sugiarto (International Journal of Society and Law, 2024)
The development of sports infrastructure in the city of Medan is an important need to support the healthy and active lifestyle of its people. In this context, this research aims to analyze strategies for developing sports infrastructure in the Medan City area with a focus on increasing accessibility, quality of facilities and use of public spaces that support sports activities. The research method used is literature study to identify infrastructure needs, SWOT analysis to evaluate strengths, weaknesses, opportunities and threats in developing sports infrastructure in Medan City. The results of this research show that the development of sports infrastructure needs to be integrated with spatial planning policies and sustainable city development. It is hoped that this research can provide guidance for policy makers in formulating strategies for developing effective and sustainable sports infrastructure in the city of Medan.